2011
DOI: 10.1038/nature09706
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan extension induced by AMPK and calcineurin is mediated by CRTC-1 and CREB

Abstract: Activating AMPK or inactivating calcineurin slows ageing in Caenorhabditis elegans1,2 and both have been implicated as therapeutic targets for age-related pathology in mammals3–5. However, the direct targets that mediate their effects on longevity remain unclear. In mammals, CREB-regulated transcriptional coactivators (CRTCs)6 are a family of cofactors involved in diverse physiological processes including energy homeostasis7–9, cancer10 and endoplasmic reticulum stress11. Here we show that both AMPK and calcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
373
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(385 citation statements)
references
References 39 publications
10
373
2
Order By: Relevance
“…When activated, AMPK negatively regulates mTOR activation (Mihaylova and Shaw 2011). AMPK activation slows aging in C. elegans (Apfeld et al 2004;Mair et al 2011) and is being considered as a calorie restriction mimetic (Ingram et al 2006). Therefore, metformin has been used for life extension in mammals and, in some studies although not all, has demonstrated gerosuppressive effects (Smith et al 2010;Anisimov et al 2011;Berstein 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When activated, AMPK negatively regulates mTOR activation (Mihaylova and Shaw 2011). AMPK activation slows aging in C. elegans (Apfeld et al 2004;Mair et al 2011) and is being considered as a calorie restriction mimetic (Ingram et al 2006). Therefore, metformin has been used for life extension in mammals and, in some studies although not all, has demonstrated gerosuppressive effects (Smith et al 2010;Anisimov et al 2011;Berstein 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, decreased CREB activity was associated with learning impairments in healthy aged animals [31,32] and with cognitive deficits in animal models of neurodegenerative disorders [33][34][35]. Importantly, the level of phosphorylated CREB and the activity-induced increase in CREB phosphorylation is diminished in ageing [36,37], and this itself may influence the ageing process [38,39]. Altered calcium signalling in ageing neurons significantly contributes to diminished CREB activity.…”
Section: Functional Histological and Molecular Changes In The Ageingmentioning
confidence: 99%
“…These changes may lead to an enhanced calcium signal after activation and elevated activity of calcium-dependent signalling pathways. Agedependent alterations in the intracellular signalling system have a huge impact on the transcriptional activity of the cells [30,38,45].…”
Section: Functional Histological and Molecular Changes In The Ageingmentioning
confidence: 99%
“…Deletion of TORC, the single CRTC homolog in Drosophila, reduces fat stores and increases sensitivity to starvation (11). CRTCs also seem to be important in aging: RNAi-mediated depletion of CRTC1 in Caenorhabditis elegans extends lifespan, in part through down-regulation of the CREB pathway (12).…”
mentioning
confidence: 99%